Biocompatibility Issues of Next Generation Decellularized Bioprosthetic Devices. (12th May 2014) - Spina, Michele; Naso, Filippo; Zancan, Irene; Iop, Laura; Dettin, Monica; Gerosa, Gino
Abstract : With respect to the limited lifespan of glutaraldehyde-treated bioprostheses (BHVs) to date there is almost no alternative when heart valve replacement surgery is required and most advanced current research attempts to develop tissue engineered valve scaffolds to be implanted in vivo or after in vitro preconditioning and dynamic seeding with host cells. However the clinical outcomes of grafting detergent-based cell-depleted tissue engineered xenogeneic constructs are still controversial. Insufficient quantitative evaluations performed at preclinical level about the residual content of xenogeneic epitopes, detergents, and nucleic acid materials in such scaffolds have led to disappointing and disastrous results. The risk of these dramatic accidents reoccurring remains very high unless safety and reliable control tools aimed to reach their complete removal, in order to consider tissues biocompatible and suitable for clinical practice.